(untitled) (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2026)
The ecological function of green open spaces (GOS) in urban areas as CO2 absorbers is very important. Motor vehicle transportation increases every year and is one of the largest contributors to CO2 emissions in urban areas. The presence of urban green open spaces such as the Alun-alun Kota Bogor is vital for maintaining the balance between urban CO2 emission concentrations and the carbon absorption capacity of vegetation within urban green open spaces. The objective of this study is to evaluate the role of Alun-Alun Kota Bogor as an urban green open space in functioning as a carbon sink by comparing CO₂ emissions generated from surrounding transportation activities with the carbon absorption capacity of existing vegetation. The analytical methods used include descriptive quantitative analysis, encompassing CO2 emission quantification using the Intergovernmental Panel on Climate Change (IPCC) analysis method, CO2 absorption capacity analysis of vegetation using the absorption capacity analysis method, and descriptive analysis to formulate evaluative recommendations based on vegetation recommendations from Ministry of Public Works Regulation No. 5 of 2008 and previous studies. The results indicate that existing vegetation has limited capacity to offset transportation-related CO₂ emissions, suggesting the need for vegetation intensification to enhance the ecological function of the square.